THE USE OF SENTENCE OUTLINE TO IMPROVE STUDENTSâ WRITING ABILITY - Qalby, Nur; Ivery, Adil (Lembaga Perpustakaan Unismuh Makassar, 2013)
The research questions of this research were how does sentence outline improve the students of the second year of SMP Negeri 4 Sungguminasa ability to write paragraph? The researcher used A Classroom Action Research (CAR). The aims of this research are to find out the improvement of studentsâ writing skill and their activeness in learning process through Writing Process Approach. Two cycles had been conducted, where each cycle consisted of four meetings. It employed writing test as instrument. A number of subjects of the research were 42 students in the second grade conducted of 31 women and 11 men. The researcher took real data from the school to know the studentsâ writing ability. The results of the students writing test in cycle 1 and cycle 2 had increased in different scores.Â There was increasing by students at the end action of second cycle. The research findings indicated that use of writing process approach could increase the studentsâ writing skill. The means scores of students in Diagnostic test was 59.84 became 66.64 in cycle 1, and after revision in the cycle 2 the mean score in cycle 2 was 70.79 by implemented of sentence outline. The successful of minimal criteria (KKM) was 65 while cycle 1, there were 2 (4.76%) students get poor, 27 (64.29%) get fair, and 13 (30.95%) get good meant that students who achieved the successful minimal criteria (KKM) more than a half of them. In cycle 2 there was 25 (59.52%) get fair and 17 (40.48%) get fair.Keyword: Sentence, outline, improve, ability.Pertanyaan penelitian pada penelitian ini adalah bagaimana kalimat garis meningkatkan kemampuan siswa SMP Negeri 4 Sungguminasa untuk menulis Paragrap. Peneliti menggunakan Penelitian Tindakan Kelas (PTK). Tujuan dari penelitian ini adalah untuk mengetahui peningkatan kemampuan menulis siswa dan keaktifan mereka dalam proses belajar melalui Pendekatan Menulis Proses. Dua siklus telah dilakukan, di mana setiap siklus terdiri dari empat pertemuan. Ini digunakan tes menulis sebagai instrumen. Sejumlah subyek penelitian adalah 42 siswa di kelas dua yang dilakukan dari 31 perempuan dan 11 laki-laki. Peneliti mengambil data ril dari sekolah untuk mengetahui kemampuan menulis siswa. Hasil tes menulis siswa pada siklus 1 dan siklus 2 meningkat dinilai yang berbeda. Ada meningkat siswa pada tindakan akhir siklus kedua. Hasil penelitian menunjukkan bahwa penggunaan pendekatan proses menulis dapat meningkatkan kemampuan menulis siswa. Skor siswa dalam tes diagnostik adalah 59,84 menjadi 66,64 pada siklus 1, dan setelah revisi pada siklus 2 nilai rata-rata pada siklus 2 adalah 70,79 dengan menerapkan kalimat garis besar. Kriteria Keberhasilan Minimal (KKM) adalah 65 sedangkan siklus 1, ada 2 (4,76%) siswa mendapatkan kruang, 27 (64,29%) mendapatkan cukup, dan 13 (30,95%) mendapatkan baik berarti bahwa siswa yang mencapai Kriteria Keberhasilan Minimal (KKM) lebih dari setengah dari mereka. Dalam siklus 2 ada 25 (59,52%) mendapatkan cukup dan 17 (40,48%) mendapatkan cukup. Kata Kunci: Kalimat, garis besar, meningkatkan, kemampuan.